Developments in treatments for amyotrophic lateral sclerosis via intracerebroventricular or intrathecal delivery. (July 2014) - Van Damme, Philip; Robberecht, Wim
<x xml:space="preserve">Abstract</x> Introduction: Amyotrophic lateral scleroses (ALS) are neurodegenerative disorders primarily affecting the motor system. These incurable disorders are relentlessly progressive and typically limit survival to 2 – 5 years after disease onset. An improved knowledge about disease-causing genes, disease proteins and pathways has revealed considerable heterogeneity in ALS. Novel targeted therapies are being developed, but getting these beyond the BBB remains a challenge. Areas covered: The authors review the intracerebroventricular and intrathecal delivery of drugs for the treatment of ALS in preclinical and clinical studies. Expert opinion: Lack of BBB permeability should not hold back the development of promising treatments for ALS, as the available evidence suggest that direct intrathecal or intracerebroventricular administration of drug is a feasible delivery route in patients with ALS.